Equity in Tax Law: Vietnam Case Study - Le Thi Thao; Nguyen Thi Trien (Fakultas Hukum Universitas Lampung, 2022)
One of the prime principles in the optimal tax system of countries is fairness. Equity in tax law originates from two points of view: fairness on the principle of benefits (from which taxpayers take away from society) and fairness on the principle of the ability to pay taxes (income). According to economist Adam Smith,